2017
DOI: 10.1007/s11010-017-3121-y
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and VEGFR1 levels in different regions of the normal and preeclampsia placentae

Abstract: Altered placental angiogenesis is implicated in the pathophysiology of preeclampsia. We have earlier reported placental regional differences in oxidative stress markers and neurotrophins. Oxidative stress and neurotrophins are reported to regulate angiogenesis. This study aims to examine protein and mRNA levels of vascular endothelial growth factor (VEGF) and VEGF receptor 1 (VEGFR1) in four regions [central maternal (CM), central fetal (CF), peripheral maternal (PM), and peripheral fetal (PF)] of the placenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…This finding is related to the in vivo vasodilator effect of Gal-13 (181184). In this context, reduced Gal-13 and Gal-14 expression may play a role in the disturbed vascular changes in preterm preeclampsia (58, 185194). All our data discussed above support the idea that Gal-13 and Gal-14 also have immunoregulatory and vascular effects, as found for galectin-1 or galectin-3 (195, 196).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is related to the in vivo vasodilator effect of Gal-13 (181184). In this context, reduced Gal-13 and Gal-14 expression may play a role in the disturbed vascular changes in preterm preeclampsia (58, 185194). All our data discussed above support the idea that Gal-13 and Gal-14 also have immunoregulatory and vascular effects, as found for galectin-1 or galectin-3 (195, 196).…”
Section: Discussionmentioning
confidence: 99%
“…It should be highlighted how all these pathological conditions affect the process of angiogenesis. Placental growth factor (PIGF) has an important role in angiogenesis, as well as in the proper function of the placenta [16,17]. In women with CVD during pregnancy, overexpression of vascular endothelial growth factor (VEGF) has been reported, explaining its role in the disease's pathogenesis [12].…”
Section: Introductionmentioning
confidence: 99%
“…The association of HIF with vascular diseases during pregnancy is well known; numerous studies have clarified its important role in the pathogenesis of diseases such as preeclampsia [1012]. One of the key points in the regulation of these processes is the angiogenic inducer vascular endothelial growth factor (VEGF), which plays a role in alterations in placental pathology [13]. Recent studies have indicated a decrease in transforming growth factor- β (TGF- β ) in the placenta of women with preeclampsia [14].…”
Section: Introductionmentioning
confidence: 99%